Web application for data collection in marketing strategies: an approach from the perspective of Digital Humanities - Cruz, Aldine do Socorro Corrêa; Alvarez, Edgar Bisset; Vital, Luciane Paula (EAI Endorsed Transactions on Scalable Information Systems, 2022)
INTRODUCTION: Web applications and information systems are predominantly constituted as platforms for acquiring data and services over the Internet. Such applications integrate a technological context filled with intelligent devices interactive amongst themselves, connected to the network, hardware, and software, and accessible to the most varied social segments. OBJECTIVES: This article aims to present a digital mechanism based on product marketing for the acquisition of personal data used by a company in the cosmetics industry; to characterize privacy and data protection in view of the regulatory acts prevailing in Brazil; as well as to discuss how such scenarios affect the consumer. METHODS: We performed a bibliographic survey with a qualitative approach to the information collected, and used a digital platform for commercial operation as object to analysis. RESULTS: We confirmed the use of a digital platform, accessible by different electronic devices, to spread commercial content reaching a considerable volume of users, which then propagated it. We verified an indirect relationship of supply of goods through the transfer of identification, communication and location data. We identified users being directed to the Terms of Promotion and User Privacy Policy, as well as different media resources aiding their understanding. CONCLUSION: The customer’s vulnerability in consumer relations stands out, something increasingly frequent in digital environments, which enables a directly proportional flow of information between market and consumer. Finally, we observed that Digital Humanities constitute a broad field of research under an extensive methodological domain, due to its interdisciplinary character, for the digital study of cultural phenomena, and promote critical reflection on the effects that computational methods have on society.